Molecular dynamics-based descriptors of 3-O-Sulfated Heparan sulfate as contributors of protein binding specificity. (August 2022) - Danielsson, Annemarie; Kogut, Małgorzata M.; Maszota-Zieleniak, Martyna; Chopra, Pradeep; Boons, Geert-Jan; Samsonov, Sergey A.
Abstract: Glycosaminoglycans are linear periodic and anionic polysaccharides found in the extracellular matrix, involved in a range of key biochemical processes as a result of their interactions with a variety of protein partners. Due to the template-less synthesis, high flexibility and charge of GAGs, as well as the multipose binding of GAG ligands to receptors, the specificity of GAG-protein interactions can be difficult to elucidate. In this study we propose a set of MD-based descriptors of unbound Heparan Sulfate hexasaccharides that can be used to characterize GAGs and explain their binding affinity to a set of protein receptors. With the help of experimental data on GAG-protein binding affinity, we were able to further characterize the nature of this interaction in addition to providing a basis for predictor functions of GAG-protein binding specificity. Graphical Abstract: ga1 Highlights: Deeper insight into the specificity of heparan sulfate-protein binding. Physicochemical descriptors of heparan sulfate linked to binding affinity. Molecular dynamics of heparan sulfate used for binding specificity determination. Principal component analysis of physico-chemical descriptors of heparan sulfate.